Essential oil composition of aerial parts of two Salvia L.(S. russellii Bentham and S. bracteata Banks & Sol.) species - Dogan, Gülden; Demirpolat, Azize; Bagci, Eyup (Chemical Publishing Co., 2014)
In this study, essential oil composition of the aerial parts of two Salvia L. (Salvia russellii Bentham and Salvia bracteata Banks & Sol.) from East Anatolian region of Turkey were analyzed by GC and GC-MS system. The essential oils of the aerial parts of two Salvia L. (S. russellii and S. bracteata) collected from the Turkey were obtained by hydrodistillation, in 0.8 % (v/w) and 0.7 (v/w) oil yields, respectively. Thirty two and fifty five components were identified representing 98.5 and 91 % of the oils, respectively. The major constituents of S. russellii were thymol (31.9 %) ?-terpinol (13.1 %), ?-terpinene (12.5 %), whereas those S. bracteata were caryophyllene oxide (17.8 %), b-caryophyllene (16.7 %) and ?-pinene (10.5 %).
Keywords: Chemotaxonomy; Essential oil; GC-MS; Lamiaceae; Salvia